O jasnej i powierzchownej znajomości konwencji genologicznej = On clear and superficial knowledge of a genre convention - Borawski, Stanisław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Each use of language has two dimensions: individual and social. The linguistic message is a collection of linguistic signs of different levels: phonetic-phonological, morphological, syntactic and genealogical. The mentioned order reflects the increasing level of difficulty resulting in the difference in the scope of the bilateral and multilateral negotiation of the language code.
Keywords: wspólnota komunikatywna; forma i funkcja; konwencja genologiczna; entropia; kodowanie; deszyfracja; obyczaj językowy; communicative community; form and function; genological convention; entropy; coding; decryption; linguistic custom